2012
DOI: 10.1002/stem.780
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Fate Mapping Identifies Mesenchymal Progenitor Cells

Abstract: Adult mesenchymal progenitor cells have enormous potential for use in regenerative medicine. However, the true identity of the progenitors in vivo and their progeny has not been precisely defined. We hypothesize that cells expressing a smooth muscle α-actin promoter (αSMA) directed Cre transgene represent mesenchymal progenitors of adult bone tissue. By combining complementary colors in combination with transgenes activating at mature stages of the lineage we characterized the phenotype and confirmed the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
287
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(307 citation statements)
references
References 26 publications
19
287
1
Order By: Relevance
“…Although most studies were conducted with bone marrow derived mesenchymal progenitor cells (MPCs), other tissues have been described to contain osteoprogenitor cells with similar regenerative potential including adipose tissue, muscle, umbilical cord blood, periosteum, dental pulp and periodontal ligament [4,[39][40][41][42][43][44][45]. The multilineage differentiation ability, paracrine effects and immunomodulatory properties of MPCs make them an ideal for tissue engineering and regenerative purposes [5,7,[46][47][48].…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Although most studies were conducted with bone marrow derived mesenchymal progenitor cells (MPCs), other tissues have been described to contain osteoprogenitor cells with similar regenerative potential including adipose tissue, muscle, umbilical cord blood, periosteum, dental pulp and periodontal ligament [4,[39][40][41][42][43][44][45]. The multilineage differentiation ability, paracrine effects and immunomodulatory properties of MPCs make them an ideal for tissue engineering and regenerative purposes [5,7,[46][47][48].…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Descendants of Wnt-Responding Osteolineage Cells Contribute to Bone Injury Repair. Recent studies have shown that progenitors of the osteolineage can participate in bone tissue repair (18)(19)(20)22). Thus, in addition to lineage tracing during homeostasis, we probed for progenitor activity in the AXCT2-traced population by asking if the progeny of neonatal AXCT2-labeled cells could contribute to bone injury repair in adulthood.…”
Section: Neonatal Wnt-responding Stromal Population Contains Progenitorsmentioning
confidence: 99%
“…Osteolineage cells arise from multipotent mesenchymal progenitors, which subsequently give rise to osteolineage-restricted progenitors (18)(19)(20)(21)(22)(23). In perinatal mice, Osterix (Osx) appears to be expressed by both populations (20,21,24) and continues to be expressed as the cells divide and differentiate into osteoblasts.…”
mentioning
confidence: 99%
“…We compared LacZ expression in Sostdc1 -/-and Sostdc1 -/+ calluses using an antibody specific for its gene product, β-galactosidase. Nestin is a mesenchymal cell marker used in flow cytometry to identify mesenchymal stem cell populations [191] and α-SMA marks progenitor cells that can differentiate into chondrocytes and osteoblasts [174]. β-galactosidase antibody stain ( Fig.…”
Section: Sostdc1 Marks a Population Of Osteochondral Progenitor Cellsmentioning
confidence: 99%
“…Optimal fracture repair requires contribution from surrounding tissues, yet we know very little about the interactions between bone, muscle, vasculature, and the periosteum [173][174][175]. In particular the periosteum, a thin tissue that covers the outer cortical bone surface, contains a reservoir of progenitor cells that contribute to bone repair; further, periosteal grafts and alpha-smooth muscle actin (α-SMA)-positive cells integrate into the callus after fracture [105,175].…”
Section: Introductionmentioning
confidence: 99%